A plasmon-enhanced theranostic nanoplatform for synergistic chemo-phototherapy of hypoxic tumors in the NIR-II window. Issue 32 (20th July 2021) - Chen, Ming-Ming; Hao, Hai-Li; Zhao, Wei; Zhao, Xueli; Chen, Hong-Yuan; Xu, Jing-Juan
Abstract : A plasmon-enhanced theranostic nanoplatform for synergistic chemo-phototherapy (PTT/PDT) of hypoxic tumors in the NIR-II window. Abstract : Development of simple and effective synergistic therapy by combination of different therapeutic modalities within one single nanostructure is of great importance for cancer treatment. In this study, by integrating the anticancer drug DOX and plasmonic bimetal heterostructures into zeolitic imidazolate framework-8 (ZIF-8), a stimuli-responsive multifunctional nanoplatform, DOX-Pt-tipped Au@ZIF-8, has been successfully fabricated. Pt nanocrystals with catalase-like activity were selectively grown on the ends of the Au nanorods to form Pt-tipped Au NR heterostructures. Under single 1064 nm laser irradiation, compared with Au NRs and Pt-covered Au NRs, the Pt-tipped Au nanorods exhibit outstanding photothermal and photodynamic properties owing to more efficient plasmon-induced electron–hole separation. The heat generated by laser irradiation can enhance the catalytic activity of Pt and improve the O2 level to relieve tumor hypoxia. Meanwhile, the strong absorption in the NIR-II region and high- Z elements (Au, Pt) of the DOX-Pt-tipped Au@ZIF-8 provide the possibility for photothermal (PT) and computed tomography (CT) imaging. Both in vitro and in vivo experimental results illustrated that the DOX-Pt-tipped Au@ZIF-8 exhibits remarkably synergistic plasmon-enhanced chemo-phototherapy (PTT/PDT) and successfully inhibited tumor growth. Taken together, this work contributes to designing a rational theranostic nanoplatform for PT/CT imaging-guided synergistic chemo-phototherapy under single laser activation.